DEVELOPMENT AND VALIDATION OF TEACHER’S CULTURAL IDENTITY SCALE IN EFL CONTEXT: A STRUCTURAL EQUATION MODELING APPROACH - KHANY, REZA; GHASEMI, FIAN (Innovare Journal of Education, 2021)
Due to the importance of culture in each society, several researchers have offered different definitions. Several studies have also been conducted on language, ego, ethnic, national, religious and modern identity. However, no validated model is proposed for Iranian cultural identity in English Foreign Language (EFL) contexts. Therefore, this research constitutes a relatively new area through developing and validating teacher’s cultural identity scale in the EFL context. Drawing on existing literature and various categorization of culture, the researchers used different sources, including Persian literature, social and cultural education, theology and history books to extract different components of culture. One hundred and thirty items were created primarily based on operational deﬁnitions of each component. The items were reviewed by a group of experts. After reviewing the items, the researchers piloted and tested the questionnaire using a sample of 305 EFL teachers. A final model of Iranian cultural identity with fifty-eight items underlying the eleven-factor model was specified in exploratory and confirmatory factor analysis. The reliability of items with Cronbach’s alpha (a=0.864) for the whole instrument was found to be adequate. Furthermore, the convergent and discriminate validity of the items has been found to be satisfactory.